Efficacy and Safety of Simultaneous Integrated Boost Intensity-Modulation Radiation Therapy Combined with Systematic and Standardized Management for Esophageal Cancer - Deng, Wenzhao; Zhang, Xueyuan; Su, Jingwei; Song, Chunyang; Xu, Jinrui; Zhao, Xiaohan; Shen, Wenbin (Frontiers in Surgery, 2022)
Objective: Analyze and compare the efficacy and safety of simultaneous integrated boost intensity-modulation radiation therapy (SIB-IMRT) combined with systematic and standardized management for esophageal cancer. Methods: From January 2012 to January 2019, 200 cases of esophageal cancer patients treated with radical chemoradiotherapy in our hospital were treated with lymphatic drainage area radiation prevention combined with systematic and standardized management. According to the difference in radiotherapy methods, the patients were divided into local lesion 92 cases treated with simultaneous integrated boost intensity-modulation radiation therapy (SIB-IMRT) combined with systematic standardized management (SIB-IMRT group), and late course boost intensity-modulation radiation therapy (LCB-IMRT) combined with systematic standardized management 108 cases (LCB-IMRT group). The short-term curative effects of the two groups were compared. The dose volume parameter of the organ at risk is evaluated based on the dose volume histogram. The related adverse reactions of the two groups during chemoradiotherapy were compared. The local control rate and survival rate of the two groups were compared. Results: The recent total effective rates of rats in the SIB-IMRT group and LCB-IMRT group were 95.65% and 90.74%, respectively, and there was no significant difference between the two groups (P>0.05). The mean doses to left and right lung, heart and spinal cord in the SIB-IMRT group were significantly lower than that in the LCB-IMRT group (P<0.05). There was no significant difference in the incidence of adverse reactions such as radiation esophagitis, radiation pneumonitis, radiation tracheitis, gastrointestinal reaction and bone marrow suppression between the SIB-IMRT group and LCB-IMRT groups (P>0.05). The one-year and three-year overall survival rates in the SIB-IMRT group and LCB-IMRT groups were 82.61%, 42.39% and 77.78%, 34.26%, respectively, and the median survival times were 38 and 29 months, respectively. The local control rates in the SIB-IMRT group and LCB-IMRT group in one and three years were 84.78%, 56.52% and 75.93%, 41.67%, respectively. Conclusion: SIB-IMRT combined with systematic and standardized management in the treatment of esophageal cancer can reduce the amount of some organs at risk and improve the local control rate of the lesion.